Dylematy zdrowotne Polaków - Biernacki, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Good health ensures comfort, so it is a good thing that directly affects the well-being and quality of life of the people and society as a whole, and gives you the opportunity to work, which is a direct factor of the both individual and society permanent welfare. The aim of the article is to identify the “health dilemmas” existing in Poland from the point of view of the citizen (person) and state authority. In support of these theses, the results of questionnaires on important factors of life of Poles (Social Diagnosis, CBOS), data describing the state of health, factors influencing the health of Poles (GUS, WHO) and public healthcare expenditures in international comparison were analyzed
Keywords: stan zdrowia; opieka zdrowotna; zdrowy tryb życia